Allergic disease and risk of stress in pregnant women: a PreventADALL study. Issue 4 (13th October 2020) - Olsson Mägi, Caroline-Aleksi; Bjerg Bäcklund, Anders; Lødrup Carlsen, Karin; Almqvist, Catarina; Carlsen, Kai-Håkon; Granum, Berit; Haugen, Guttorm; Hilde, Katarina; Lødrup Carlsen, Oda C.; Jonassen, Christine Monceyron; Rehbinder, Eva Maria; Sjøborg, Katrine D.; et al.
Background: Maternal stress during pregnancy may negatively affect the health of mother and child. We therefore aimed to identify the proportion of women reporting high maternal stress in mid and late pregnancy and explore whether symptoms of maternal allergic disease are associated with perceived maternal stress in late pregnancy. Method: The population-based Preventing Atopic Dermatitis and Allergy in Children (PreventADALL) study enrolled 2697 pregnant women at their 18-week routine ultrasound examination in Norway and Sweden. Information about sociodemographic factors, symptoms and doctor-diagnosed asthma, allergic rhinitis, atopic dermatitis, food allergy, and anaphylaxis and stress using the 14-item perceived stress scale (PSS) was collected at 18 weeks (mid) and 34 weeks (late) pregnancy. High stress was defined as a PSS score ≥29. Scores were analysed using multivariate logistic and linear regression. Results: Among the 2164 women with complete PSS data, 17% reported asthma, 20% atopic dermatitis, 23% allergic rhinitis, 12% food allergy and 2% anaphylaxis. The proportion of women reporting high stress decreased from 15% at mid to 13% at late pregnancy (p<0.01). The adjusted odds ratio for high stress in late pregnancy was 2.25 (95% CI 1.41–3.58) for self-reported symptoms of asthma, 1.46 (95% CI 1.02–2.10) for allergic rhinitis and 2.25 (95% CI 1.32–3.82) for food allergy. A multivariate linear regression model confirmed that symptoms of asthma (β coefficient 2.11; 0.71–3.51), atopic dermatitis (β coefficient 1.76; 0.62–2.89) and food allergy (β coefficient 2.24; 0.63–3.84) were independently associated with increased PSS score. Conclusion: Allergic disease symptoms in pregnancy were associated with increased stress, highlighting the importance of optimal disease control in pregnancy. In this population-based study, high stress was reported by 15% in mid-pregnancy and in 13% at late pregnancy. High stress in late pregnancy was associated with symptoms of asthma, allergic rhinitis and food allergy. https://bit.ly/3faKmwh